2019
DOI: 10.1027/1864-9335/a000362
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Double Standard in the Real World

Abstract: Abstract. The sexual double standard (SDS) has traditionally been studied by examining evaluations of hypothetical targets. Although much knowledge has been gained regarding the SDS by using this methodology, the literature thus far has suffered from a lack of ecological validity. The goal of the present study was to determine whether the SDS emerged in evaluations of participants’ real-life friends and acquaintances. Participants ( n = 4,455) evaluated a single, randomly assigned male or female friend or acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 54 publications
2
16
1
1
Order By: Relevance
“…In summary, our findings for men indicated that they still supported the traditional double standard, and this pattern is consistent with previous studies [4,36]. However, for the sample from Spain, but not from Colombia, our findings indicated support for the recently so-called "reverse" sexual double standard; that is, more sexual reluctance for men than for women.…”
Section: Emergence Of a Reverse Form Of The Sexual Double Standardsupporting
confidence: 91%
See 2 more Smart Citations
“…In summary, our findings for men indicated that they still supported the traditional double standard, and this pattern is consistent with previous studies [4,36]. However, for the sample from Spain, but not from Colombia, our findings indicated support for the recently so-called "reverse" sexual double standard; that is, more sexual reluctance for men than for women.…”
Section: Emergence Of a Reverse Form Of The Sexual Double Standardsupporting
confidence: 91%
“…On a psychological level, the relevance of its clinical effects is worth highlighting. SDS has been associated with psychological trauma [5], worse sexual health, and an increased risk of contracting sexually transmitted infections [4,6]. From a social point of view, the effect of SDS can take place through macrosocial processes, for example, the social norms that regulate the behavior of men and women, and define what are the appropriate behaviors for each gender, in the field of heterosexual behaviors [7].…”
Section: Psychological and Social Effects Of The Sexual Double Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many other fields of sexuality are affected by the presence of a DS, the number of sexual partners being another relevant example (Ramos et al, 2005;Bordini & Sperb, 2013;Sprecher et al, 2013). Very recently, Marks et al (2019) asked a sample of about 5000 US young people, aged 18-35, to evaluate the sexual behaviour of one of their friends whose sexual life they knew. The results show the emergence of a strong DS, in particular with respect to the number of sexual partners, with women evaluated worse than men as the number of partners increases.…”
Section: Related Literaturementioning
confidence: 99%
“…Level of endorsement of the SDS has been found to be associated with the judgement of sexual behavior of both close friends and more distant acquaintances (Marks et al, 2019). Endorsement of (aspects of) the sexual double standard has also been associated with a variety of negative sexual health outcomes (Sanchez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%